Periodontite apical induzida em dentes de cães : avaliação histológica da endodontia em sessão única empregando-se sterilox e hipoclorito de sódio, associados ou não à terapia fotodinâmica, e acurácia dos exames radiológico, tomográfico e histológico no seu diagnóstico - Lopez, Fernanda Ullmann (2014)
The persistence of infection within the root canal system is one of the main factors responsible for endodontic failures. The complexity of the internal anatomy of root canals prevents its complete removal by current instrumentation techniques. Thus, alternative disinfection protocols, including irrigating solutions and photo-activated therapy (PAD), have been acessed. In this study, 10 dogs were randomly divided into two groups (n= 5): with and without PAD. The canals of upper and lower premolars of each dog were distributed in the experimental subgroups: SX (400ppm Sterilox), H2 (2% sodium hypochloride (NaOCl)), H5 (5% NaOCl) and C+ (positive control: saline solution) in a total sample of 134 root canals. Teeth of the experimental and C+ groups were opened and the canals were left exposed to the oral environment for 15 days and then sealed for apical periodontitis (AP) induction. After 60 days, the root canals were treated in accordance with each disinfection protocol proposed and filled in the same session. After 120 days, the dogs were euthanized and the following procedures were carried out: periapical radiography (PR), to measure the AP area; cone beam computed tomography (CBCT), to measure the AP area and volume; light microscopy, to evaluate inflammatory periapical events. Based on the colected data, the study was divided into two papers. The first carried out an evaluation of the efficacy of 400ppm Sterilox, 2%NaOCl and 5%NaOCl, with and without PAD, in a single visit root canal treatment of dog s teeth with AP. In the histological evaluation, scores were given according to the intensity of inflammatory infiltrate. Data was colected and analized statistically with Kruskall-Wallis and Mann-Whitney tests (α= .05). The PAD did not produce significant differences in the scores for apical inflammation when used after chemo-mechanical preparation. The irrigating solutions SX, H2 and H5 without PAD were statistically different from SS (P<0,05) that presented the greatest scores for apical inflammation. In conclusion, PAD did not show any clinical relevance for the treatment of root canal with pulpal necrosis and AP. The use of 400 ppm Sterilox in the chemo-mechanical preparation provided efficient cleaning and may be considered an alternative to NaOCl in root canal treatment. The second paper investigated the correlation and agreement between PR (area) and CBCT (area and volume) data, correlating with the correspondig histopathological data. The correlation between methods was evaluated by Pearson's coefficient and Bland-Altman's (BA) method was used to assess the agreement between PR and CBCT data. The results showed that, despite a strong correlation between PR and CBCT areas, the limits of agreement were very broad (95%: 0.19 to 1.08). PR only measured on average 63% of CBCT values. Although the strong correlation between PR area and CBCT volume, BA suggests that the larger the CBCT volume the more underestimated the PR value. When APs had volumes smaller than 6 mm3, the PR estimates of CBCT data were unpredictable. The correlation between PR area, CBCT area, CBCT volume and histology data was significant. In conclusion, the diagnosis of AP based on PR data is clinically limited and it should not be used for scientific investigations.